Influence of Species and Size on Weight Loss during Thawing of Frozen Shrimps - T.N., Venugopal (Fishery Technology, 2025)
Weight loss of two species of frozen shrimps viz. Parapenaeopsis stylifera andÂ Metapenaeus dobsoni packed as peeled and undeveined and as has peeled and deveined were studied. ln both species weight loss inaeased as the size of the shrimps decreased and thedifference in weight loss of large and small shrimp was found significant in both PD and PUD. Between the two species there were no significant differences in weight loss in both PD and PUD meat of same size grades except in PUD 2(1)/3(1) grade.